2020
DOI: 10.1007/s10495-020-01597-2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal paracentesis drainage attenuates severe acute pancreatitis by enhancing cell apoptosis via PI3K/AKT signaling pathway

Abstract: Our previous studies have shown that abdominal paracentesis drainage (APD) is a safe and effective strategy for patients with severe acute pancreatitis (SAP). However, the underlying mechanisms behind APD treatment remain poorly understood. Given that apoptosis is a critical pathological response of SAP, we here aim to investigate the effect of APD on cell apoptosis in pancreatic tissues during SAP and to explore its potential molecular mechanism. SAP was induced by 5% sodiumtaurocholate retrograde while APD g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…A previous study demonstrated that Akt activity is responsible for as much as 80% of neurotrophin-regulated cell survival, indicating that Akt is the major survival-promoting protein for neurons (38). Akt signaling inhibits apoptosis by regulating the expression of Bcl-2 and Bax and finally, the expression of caspase-3 (39,40). The findings of the present study were consistent with those of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated that Akt activity is responsible for as much as 80% of neurotrophin-regulated cell survival, indicating that Akt is the major survival-promoting protein for neurons (38). Akt signaling inhibits apoptosis by regulating the expression of Bcl-2 and Bax and finally, the expression of caspase-3 (39,40). The findings of the present study were consistent with those of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 92%
“…The regulation of PI3K signaling is crucial for maintaining cellular and metabolic function in both cancerous and normal cells. Apart from metabolic processes, several cellular functions, such as cell cycle regulation, cell growth, proliferation, migration, and death (apoptosis) are influenced by PI3K signaling regulation [87][88][89][90]. P13K responds to extracellular stimuli and regulates the intracellular signaling cascade involving Akt, NFκB, p53, and mTOR to achieve its role in cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…It has confirmed that Bmf can function as apoptosis activator ( Hayakawa et al, 2016 ) and Gab1 can plays a central role in cell growth, transformation and apoptosis ( Zhang et al, 2019b ). Reportedly, apoptosis has protective effects on SAP ( Luo et al, 2020 ). Therefore, we speculate that lncRNA AK004187 and lncRNA uc029sug.1 could influence the severity of the disease by regulating the apoptosis of acinar cells in SAP.…”
Section: Discussionmentioning
confidence: 99%